2016
DOI: 10.5007/1980-0037.2016v18n3p371
|View full text |Cite
|
Sign up to set email alerts
|

Determinantes táticas do jogo praticado pelo atacante central no voleibol masculino

Abstract: -Among volleyball skills, spike is responsible for the highest number of scores, and the first tempo of attack is related to the higher incidence of score a point, by hindering the defensive opponent's action. However, most of the studies show general results and do not specify the conditions and constraints of each attack zone. Thus, the aim of this study was analyzing the offensive game (complex I) performed by the middle attacker at the 2014/2015 National men's Brazilian Championship (Superliga). The sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 13 publications
2
11
0
1
Order By: Relevance
“…Nevertheless, these differences apply to the findings of both studies as well. Whereas Fellingham et al (2013) found no data indicating differences of success depending on the type of first tempo attack, Costa et al (2016) found that positive and negative sets were associated (p<.001) with attack score (obtaining a point), and inside shoot sets were associated with attack error (losing a point) and a poor reception (p<.001). Additionally, the tip was associated (p<.001) with inside shoot and back one set.…”
Section: Attackmentioning
confidence: 91%
See 2 more Smart Citations
“…Nevertheless, these differences apply to the findings of both studies as well. Whereas Fellingham et al (2013) found no data indicating differences of success depending on the type of first tempo attack, Costa et al (2016) found that positive and negative sets were associated (p<.001) with attack score (obtaining a point), and inside shoot sets were associated with attack error (losing a point) and a poor reception (p<.001). Additionally, the tip was associated (p<.001) with inside shoot and back one set.…”
Section: Attackmentioning
confidence: 91%
“…Fellingham et al (2013) describe the quick as an attack performed close to the setter, either in front of or behind him, and the gap as an attack executed approximately 3 metres from the left sideline. On the other hand, Costa et al (2016) divide the quick by Fellingham et al (2013) into three different possibilities: positive (in front of the setter, contacting the ball on the right side of the body), negative (in front of the setter, contacting the ball on the left side of the body), back one (behind and close to the setter); and refer to the gap as inside shoot. Nevertheless, these differences apply to the findings of both studies as well.…”
Section: Attackmentioning
confidence: 99%
See 1 more Smart Citation
“…In volleyball, match analysis may be based on Game Complexes, with Complex I (KI) consisting of reception, setting, and attack, as the main focus of investigation (Hurst et al, 2016; Laporta et al, 2018a; Loureiro et al, 2017). From this perspective, analysts frequently observe a recurrent game pattern in the side-out phase of high-level volleyball (a successful point scored by the receiving team during the opponent’s serve) (Costa et al, 2016, 2016, 2016; Rocha et al, 2022). The side-out phase is characterized by receptions that enable an organized attack, setting conditions that adapt to the positions of attackers and blockers, and attacks against less structured blocks (Costa et al, 2017a, 2018; Dutra et al, 2021; Rocha et al, 2021, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…: Teor. e Pesq., Brasília, 2019, v. 35, e3538 LS Fortes, L Fiorese, JRA Nascimento-Júnior, SS Almeida, & MEC Ferreira O voleibol é um esporte coletivo do tipo intermitente, caracterizado pela imprevisibilidade (Costa et al, 2016;Fortes et al, 2018). A chave para se obter sucesso nessa modalidade concerne na escolha da melhor decisão ("o que fazer"), adotando a técnica correta ("como fazer") em um pequeno espaço de tempo e de forma acurada (Lopes, Magalhães, Diniz, Moreira, & Albuquerque, 2016).…”
unclassified